2015
DOI: 10.1002/pat.3696
|View full text |Cite
|
Sign up to set email alerts
|

Morphology evolution and crystalline structure of controlled‐rheology polypropylene in micro‐injection molding

Abstract: In this paper, the microstructural evolution of controlled-rheology polypropylene (CRPP) with different melt viscoelasticities was investigated by polarized optical microscopy, scanning electronic microscopy, differential scanning calorimeter, and wide-angle X-ray diffraction. It is found that a typical "skin-core" structure formed in CRPP microparts and the thickness of oriented layer of CRPP microparts decreases notably with the addition of peroxide. The thickness of oriented layer and the distribution of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Compared with traditional injection‐molding technology, microinjection molding has the advantages of a low cost and high production efficiency . As a result, innovative processing technology has been widely used in the production of biological probes, biological instruments, and so on . We adopted acrylonitrile butadiene styrene (ABS) to blend with PLA, used microinjection molding to produce tensile samples, and found that the addition of ABS could actively alter the samples' rheological properties .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional injection‐molding technology, microinjection molding has the advantages of a low cost and high production efficiency . As a result, innovative processing technology has been widely used in the production of biological probes, biological instruments, and so on . We adopted acrylonitrile butadiene styrene (ABS) to blend with PLA, used microinjection molding to produce tensile samples, and found that the addition of ABS could actively alter the samples' rheological properties .…”
Section: Introductionmentioning
confidence: 99%
“…Microinjection molding (µIM) has been widely adopted to prepare microcomponents, which features very high shearing and cooling effects during the mold cavity filling process [4,6,7]. Relative to the microparts made with metals, polymeric microparts can be produced at a large scale at relatively low cost per part [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the majority of cases, the studied membranes were formed under laboratory conditions. Therefore, certain phenomena taking place during the membranes production on the industrial scale, such as the row arrangement of polymer chains resulting in the formation of linear structure of the membrane matrix, can affect the polymer mechanical properties [46]. The possibilities of preventing the polymer degradation and methods for improvement of the mechanical properties of PP membranes by introducing fillers into the dope solution, are presented in this paper.…”
Section: Introductionmentioning
confidence: 99%